ANALISIS PENYELESAIAN PERSELISIHAN PEMUTUSAN HUBUNGAN KERJA PADA PENGADILAN NEGERI JAKARTA PUSAT (PUTUSAN NOMOR 67/PDT.SUS PHI/2020/PN.JKT.PST: Analysis of Termination Dispute Resolution at the Central Jakarta Districk Court ( Descision Number 67/Pdt. Sus.Phi/2020/PN.Jkt.Pst) - Ayu Widia Pertiwi; Yogo Pamungkas (Universitas Trisakti, 2024)
When handling disputes between workers and employers in industrial relations, action is required in accordance with applicable labor law. The initial step that must be taken is to carry out bipartite negotiations between the two parties to find a solution to the dispute. If bipartite negotiations are unsuccessful, the next step is to file for mediation and sue the Industrial Relations Court. The problems that arise between the Plaintiff and the Defendant relate to the mechanism for resolving disputes in termination of employment (PHK) in industrial relations, as well as whether the procedures carried out are in accordance with the statutory regulations explained in decision Number 67/Pdt.Sus-PHI/2020/ PN. JKT. PST. From this decision, it is not considered that any negotiations took place, which is the debate in this case. To answer this problem, normative juridical research was carried out with a descriptive analytical approach. This research refers to primary and secondary data which was analyzed qualitatively, and conclusions were drawn using deductive methods. The process of resolving this industrial relations case involves mediation with a mediator from the East Jakarta Social and Employment Service, as well as filing a lawsuit with the Industrial Relations Court at the local District Court. However, statutory regulations are not in accordance with the steps taken in this case, because bipartite negotiations are thought to have never occurred.